Investigating the contribution of geometry on the failure of cellular core structures obtained by additive manufacturing - Hugo Arajo; Marco Leite; A.M.R. Ribeiro; Augusto M. Deus; Luis Reis; M.F. Vaz (Fracture and Structural Integrity)
The aim of this work is to evaluate the mechanical properties and failure analysis of cellular core structures with different geometries that were obtained by additive manufacturing.